Politics of (Dis)Integration - Hinger, Sophie; Schweitzer, Reinhard (IMISCOE Research Series, 2020)
This open access book explores how contemporary integration policies and practices are not just about migrants and minority groups becoming part of society but often also reflect deliberate attempts to undermine their inclusion or participation. This affects individual lives as well as social cohesion. The book highlights the variety of ways in which integration and disintegration are related to, and often depend on each other. By analysing how (dis)integration works within a wide range of legal and institutional settings, this book contributes to the literature on integration by considering (dis)integration as a highly stratified process. Through featuring a fertile combination of comparative policy analyses and ethnographic research based on original material from six European and two non-European countries, this book will be a great resource for students, academics and policy makers in migration and integration studies.